Gênero e ambivalência sexual na ficção de Caio Fernando Abreu: um olhar oblíquo sobre Onde andará Dulce Veiga? - Anselmo Peres Alós (Estudos de Literatura Brasileira Contemporânea)
This paper aims to investigate how Caio Fernando Abreu simultaneously con- structs, represents and crashes the idea of monolithic sexual identities in his novel Onde andará Dulce Veiga? (1990). Using analytical tools from narratology and gender studies, this reading of Abreu’s novel tries to understand the role of the cultural crossings when it comes to the disruptive modes of narration of the readymade notions of Brazilian national/sexual identity.